Predictors of permanent pacemaker implantation in aortic valve diseases after TAVI with vitaFlow liberty system - Ju, Changlin; Xie, Xiangrong; Tang, Shengxin; Cao, Shiping (Frontiers in Cardiovascular Medicine, 2023)
Abstract：Permanent pacemaker implantation (PPI) is a known complication in patients with aortic stenosis following transcatheter aortic valve implantation (TAVI). However, there is limited research on TAVI for pure aortic regurgitation (PAR), and more investigation is needed to determine the occurrence of postoperative cardiac conduction block and the need for PPI in this population. Therefore, this retrospective analysis aimed to evaluate the incidence of cardiac conduction block and the necessity of PPI after TAVI in patients with different types of aortic valve disease, including pure aortic stenosis (PAS), aortic stenosis with regurgitation (ASR), and PAR. Clinical factors were examined to predict the requirement for PPI. The results demonstrated that cardiac conduction block was a common complication following TAVI, particularly in patients with aortic regurgitation. Aortic regurgitation was identified as an independent risk factor for PPI. Additionally, first-degree atrioventricular block emerged as a sensitive predictor for PPI in patients with PAR. These findings provide valuable insights into the safety and effectiveness of TAVI, which can help enhance patient management and reduce complications.